The Economic Impact of Project Risk Management on Cost Efficiency and Time Performance in Medium-Scale Construction Projects - Dewi Kartika; Bambang Setiawan (Generasi Sains Indonesia, 2025)
This study examines the economic impact of Project Risk Management on time performance and cost efficiency in medium-scale construction projects in Indonesia. Using a quantitative explanatory approach, data were collected from 123 construction professionals involved in projects with contract values ranging from IDR 10 to 100 billion. Project Risk Management was measured through indicators of risk identification, analysis, response planning, and monitoring, while project performance was assessed using time deviation and cost overrun measures. The data were analyzed using Partial Least Squares Structural Equation Modeling. The results demonstrate that Project Risk Management has a statistically significant and negative effect on both project delay and cost overrun, indicating that stronger risk governance contributes to greater schedule stability and improved budget performance. The findings further show that although the level of risk management implementation is moderate, time delays and cost overruns remain prevalent across projects, reflecting the need for deeper institutionalization of risk practices. This study contributes to the construction management literature by extending empirical evidence on risk governance to medium-scale projects in an emerging economy context. The findings imply that strengthening organizational risk management capacity is essential for enhancing project reliability, reducing economic inefficiencies, and supporting sustainable infrastructure development.